Task Design Of "Leading In English" In Candlin Perspective (1987): Task Analysis - Purnaningtyas, Wahyu, Prof. Dr. Endang Fauziati, M. Hum, Nur Hidayat, M.Pd (2014)
This study focuses on task design in a workbook entitled 'Leading in English' based on Candlin Perspective (1987). This study is aimed at describing how the tasks in the workbook entitled 'Leading in English' are designed based on the eight criteria suggested by Candlin (1987). This is a descriptive qualitative research. The data are taken from the tasks in the workbook. To collect the data, the writer uses documentary method. The data were analyzed by reading, typing, and coding the tasks; analyze the tasks based on Candlin's criteria; finding the tasks that are not appropriate with Candlin's criteria; matching the tasks with tasks model by Jane and Dave Willis; giving the percentage of the total tasks whether it is appropriate or not based on Candlin's criteria and judging whether the tasks are good or not according to Candlin's perspective. Based on the research finding, the results shows that the tasks in the workbook designed based on the eighth criteria by Candlin include completion, translation, matching, group discussion, statements and dialogues, role playing, oral interview, understanding talk and teacher, formation, language games, multiple choice, comprehension, cursory reading, constructing sentences, controlled writing, dictation, simple question, composition, short talk, and punctuation task.